Enhancing Quranic and Hadith Understanding through Collaborative Learning: A Study at MTS Raden Fatah, Tarokan, Probolinggo - Bela Ismi; Hanisa Sofyan (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to explore the effectiveness of collaborative learning in enhancing students' understanding of the Quran and Hadith at MTS Raden Fatah, Tarokan, Probolinggo. The Quran and Hadith are fundamental subjects in Islamic education, and it is essential to find innovative methods that can engage students and improve their comprehension of these texts. Collaborative learning, which encourages students to work together to solve problems and discuss ideas, has been proven to foster deeper understanding, improve critical thinking, and increase engagement. This research investigates how collaborative learning methods can be applied to Quranic and Hadith studies, focusing on student participation, comprehension, and the development of a more interactive classroom environment. The study was conducted with students from grades 7 and 8 at MTS Raden Fatah. Data were collected through a combination of pre- and post-assessments, classroom observations, and interviews with students and teachers. The pre-assessment evaluated students' initial understanding of Quranic and Hadith content, while the post-assessment measured their progress after the application of collaborative learning techniques. Classroom observations provided insight into student engagement and collaboration, while interviews gathered feedback on the learning experience. The findings of this study indicate that collaborative learning significantly enhanced students' understanding of Quranic verses and Hadith. Students demonstrated greater involvement in discussions, improved comprehension of key concepts, and a stronger ability to analyze and interpret the texts. Additionally, students reported increased motivation and a more positive attitude toward learning. This research highlights the potential of collaborative learning as an effective approach to teaching Quranic and Hadith studies, creating a more engaging and supportive learning environment.